A mechanism based transition research methodology: Bridging analytical approaches. (April 2018) - Papachristos, George
Highlights: The paper outlines a mechanism based approach for the MLP. It introduces the concept of social mechanisms and proposes a methodology for identifying them in transitions. The methodology combines case study and quantitative modeling and simulation. It is a response to part of the criticism the MLP received. The paper points out particular strengths of the methodology and implications for transitions research. Abstract: This paper is motivated by the discussion in the literature about the strengths and weaknesses of the Multi-Level Perspective framework and aims to provide a response to a number of criticisms. The paper proposes retroduction as a transition research methodology that is used to identify and test social mechanisms for their explanatory power. The methodology consists in the joint use of case study and system dynamics as modeling and simulation method. The paper discusses how the two methods are used iteratively, and each one complements the strengths and counters the weaknesses of the other. The methodology has particular strengths and implications for the agenda of issues that research on future transitions to sustainability faces currently.